JUSTIFICATION OF THE CONDITIONS OF EFFICIENT TRANSPORTATION OF WHEAT FROM THE PORTS OF UKRAINE - Vil’shaniuk, Marina; Sudnyk, Nadiia (Science-based technologies, 2023)
99% of all grain is transported from the sender in Ukraine to the recipient (for example, in Indonesia) by sea transport (39 million tons). The ports of Chornomorsk (22%), Odesa (19%), Yuzhnoye (19%) and Mykolaiv (18%) ship the most. Analysis of the ports of Ukraine and the methods of wheat transportation to them, together with the correct loading of wheat on the ship, is the key to obtaining a reliable importer of high-quality wheat in the world. Transportation of grain across Ukraine is most often carried out by the following types of transport: a) dump trucks; b) on-board grain carriers; c) grain tankers; d) grain carriers-road trains; e) barges; e) railway cars. Since Indonesia is the leading country in the import of Ukrainian wheat, this market is promising for Ukrainian grain exporters. This is due to the increase in the population in Indonesia and its economic development. Therefore, the work considered as an example the transportation of wheat to this country. The article examines the process of cargo transportation on ships of larger cargo capacity. At the same time, taking into account the peculiarities of the depths near the berths in the port, reloading takes place on the raid. There are many contracts for the transportation of wheat, which are concluded on different terms. Contracts on CIF terms with the volume of deliveries of 50,000 to 400,000 tons of various grades of wheat have gained the most popularity. In the work, it is proposed to consider 2 Ukrainian ports: the Mykolaiv sea trade port and the Southern port, since the first one has the technology of loading a ship on a raid, and the last one has exported more wheat to Indonesia in recent years. According to the contract, it is necessary to transport 300,000 tons of wheat of the 3rd class in 4 months to the port of Surabaya, which is in Indonesia. ) and "AKIJ GLORY" (Dv=76,302). Wheat is delivered from the Kirovohrad region. Loading of wheat is carried out by bulk. Since there is a draft of 10.3 m in the Mykolaiv Sea Trade Port and the Dnipro-Buzka Canal, the vessels will not be fully loaded, and reloading will be carried out at the Ochakiv Raid Terminal. The shipper, also the charterer, charters several vessels on FIOS (Free In/Out) terms, which means that loading and unloading takes place at the expense of the sender/receiver.). Freight rates and wheat prices vary. For example, in the Mykolaiv sea trade port, the sender company is "Nibulon", since they rent fields, have their own elevators, grain trucks and barges, so the selling price of wheat with delivery to the port is low. The transportation option considered in the article allows it to be used for other ports, where the ship’s draft does not allow loading at the berth, but the depths on the roadway are sufficient for ships with a larger cargo capacity. The transportation of cargo on vessels of this type allows to transport a larger batch of cargo in a shorter time, which is reflected in the cost of the cargo and the speed of delivery of the entire batch.